Perfectly Matched Layer with Mixed Spectral Elements for the Propagation of Linearized Water Waves (Communications in Computational Physics, 2020)
After setting a mixed formulation for the propagation of linearized water waves problem, we define its spectral element approximation. Then, in order to take into account unbounded domains, we construct absorbing perfectly matched layer for the problem. We approximate these perfectly matched layer by mixed spectral elements and show their stability using the "frozen coefficient" technique. Finally, numerical results will prove the efficiency of the perfectly matched layer compared to classical absorbing boundary conditions.